2004
DOI: 10.1111/j.1537-2995.2003.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo PLT increments after transfusions of WBC‐reduced PLT concentrates stored for up to 7 days

Abstract: In vitro and in vivo studies showed that LR-PCs can be stored for up to 7 days with excellent clinical results, provided that they are routinely screened for bacterial contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 28 publications
(29 reference statements)
3
43
0
Order By: Relevance
“…Because this reduction in shelf life was not based on doubt about the quality of the platelets, it was decided in 2002 to increase the shelf life of PCs again to 7 days after the successful introduction of 100% screening of PCs in the Netherlands. This was supported by the results of a clinical study by Dijkstra et al [4], showing that the corrected count increments (CCIs) after 1 and 24 h PCs stored for 7 days were comparable to those of PCs stored for 5 days. Based on in vitro quality measurements, it was already known for a long time [5][6][7] that with the improved containers for platelets, storage for up to 7 days should be no problem either for PCs derived from pooled buffy coats or for those collected by apheresis.…”
Section: Shelf Life Of Platelet Concentrates In the Netherlandssupporting
confidence: 74%
“…Because this reduction in shelf life was not based on doubt about the quality of the platelets, it was decided in 2002 to increase the shelf life of PCs again to 7 days after the successful introduction of 100% screening of PCs in the Netherlands. This was supported by the results of a clinical study by Dijkstra et al [4], showing that the corrected count increments (CCIs) after 1 and 24 h PCs stored for 7 days were comparable to those of PCs stored for 5 days. Based on in vitro quality measurements, it was already known for a long time [5][6][7] that with the improved containers for platelets, storage for up to 7 days should be no problem either for PCs derived from pooled buffy coats or for those collected by apheresis.…”
Section: Shelf Life Of Platelet Concentrates In the Netherlandssupporting
confidence: 74%
“…It is already known that the quality and effectiveness of PLTs in PCs derive from various factors like leukoreduction, 1 number of PLTs, 2,3 storage temperature, 4-6 gas exchange capabilities of the PLT storage container, 7,8 and duration of storage. 9 For PCs with PLT counts below 300 ¥ 10 9 per PC no correlation in the in vitro quality of PCs was observed between PLT count and the maximum volume of the storage container. 2 However, when the PLT count was more than 300 ¥ 10 9 per PC, on Day 7 a decreased in vitro quality was observed for PCs in 1-L polyolefin (PO) containers compared to 1.3-and 1.5-L PO containers.…”
mentioning
confidence: 80%
“…When analyzed on a continuous scale, the CCI showed a small decrease for 6-or 7-day compared to 2-to 5-day PLTs that had borderline significance for the first block, but was significantly different when all blocks were analyzed, which is in line with other studies. 14,15,25 The CCI is considered a surrogate outcome measure of PLT transfusion efficacy, which has not been clearly demonstrated to correlate with more clinically relevant outcomes such as bleeding or a longer interval between transfusions. 23,26 Various values of CCI have been used to define an adequate transfusion response, but the aim should be to raise the PLT count above the "trigger" PLT count for the transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In studies examining CCI after transfusion of PLTs stored for 6 or 7 days compared to 2 to 5 days, one trial demonstrated a significantly lower CCI after transfusion of older PLTs 14 and another a significant difference between Day 2 and Day 7 PLTs but no difference between PLTs stored for 5 days compared to 7 days. 15 A significantly shorter interval between PLT transfusions has been reported after transfusion of older PLTs by Slichter and colleagues 11 (<48 hr vs. >48 hr), Heuft and colleagues 13 (4 days vs. 5 days), and Diedrich and colleagues 14 (1-to 5-day vs. 6-or 7-day) although Triulzi and coworkers 12 found no effect of storage on transfusion interval. The efficacy of extended storage PLTs and in particular whether a lower CCI results in an increased risk of bleeding is unclear.…”
mentioning
confidence: 91%